Improving the vibration suppression capabilities of a magneto-rheological damper using hybrid active and semi-active control. (29th July 2016) - Khan, Irfan Ullah; Wagg, David; Sims, Neil D
Abstract: This paper presents a new hybrid active and semi-active control method for vibration suppression in flexible structures. The method uses a combination of a semi-active device and an active control actuator situated elsewhere in the structure to suppress vibrations. The key novelty is to use the hybrid controller to enable the magneto-rheological damper to achieve a performance as close to a fully active device as possible. This is achieved by ensuring that the active actuator can assist the magneto-rheological damper in the regions where energy is required. In addition, the hybrid active and semi-active controller is designed to minimize the switching of the semi-active controller. The control framework used is the immersion and invariance control technique in combination with sliding mode control. A two degree-of-freedom system with lightly damped resonances is used as an example system. Both numerical and experimental results are generated for this system, and then compared as part of a validation study. The experimental system uses hardware-in-the-loop to simulate the effect of both the degrees-of-freedom. The results show that the concept is viable both numerically and experimentally, and improved vibration suppression results can be obtained for the magneto-rheological damper that approach the performance of an active device.